RANCANG BANGUN PROTOTYPE DAN ANALISA PEMBANGKIT LISTRIK TENAGA UAP MENGGUNAKAN TURBIN PELTON - Dhani Alkhalefi (INOVTEK - Seri Elektro, 2025)
This study aims to design and analyze a prototype of a mini-scale Steam Power Plant (PLTU) using a Pelton turbine, with 3 kg of LPG fuel and 500 grams of charcoal briquettes. The system is equipped with a 3.57-liter boiler and automatic water filling based on water level sensors (high and low). The volume of water at full (10 cm from the base) is 2.54 liters, and when it reaches the low point (7 cm) is 1.78 liters, with a volume difference of 0.76 liters. Filling the water from bottom to high takes 90 seconds, while dropping from high to low takes 27 seconds. The test results showed that LPG fuel produced a maximum pressure of 1.42 bar and an energy of 82.82 Joules, while briquettes produced much lower pressure and power. The rotation of the Pelton turbine is connected to the DC generator via a pulley system with a ratio of 5:1. However, the results of the analysis showed that the Pelton turbine was not capable of producing continuous rotation because the steam pressure was unstable and not strong enough to sustain the impact force of the water against the blade. Therefore, it can be concluded that Pelton turbines are less suitable for use in low-pressure steam-based systems, and it is recommended to use other more suitable types of turbines, such as reaction turbines or small-scale axial turbines.